Technetium Tc 99m Dimercaptosuccinic Acid Renal Scintigraphy in Diagnosis of Urinary Tract Infections in Children with Negative Culture - Nikibakhsh, Ahmad Ali; Yekta, Zahra; Mahmoodzadeh, Hashem; Karamiyar, Mohammad; Fazel, Mehdi (Urology Journal, 2009)
Introduction: The aim of this study was to evaluate the accuracy of Technetium Tc 99m dimercaptosuccinic acid (99mTc-DMSA) renal scintigraphy in the diagnosis of urinary tract infection (UTI) in children with suspected infection but with a negative urine culture. Materials and Methods: The records of all children with suspected or definite diagnosis of UTI presented during a 2-year period were reviewed in this study. Abnormal findings on renal scintigraphy, voiding cystourethrography (VCUG), and ultrasonography were evaluated and compared between the patients with the definite diagnosis of UTI and those with suspected UTI and negative urine cultures. Results: Of 210 patients, 86 had a definite diagnosis of UTI (group 1) and 124 had suspected UTI without a positive culture (group 2). Abnormal findings on DMSA scans were seen in 76 patients (88.4%) in group 1 and 84 (67.7%) in group 2. Vesicoureteral reflux was detected by VCUG in 50% and 32.3% of the patients in groups 1 and 2, respectively. In group 2, vesicoureteral reflux was seen in 40.5% of the patients with abnormal DMSA scan. Ultrasonography findings were abnormal in 51.3% and 39.8% of the patients with abnormal DMSA scan findings in groups 1 and 2, respectively. Conclusion: According to our findings, in children with a negative urine culture and abnormal urinalysis, 99mTc-DMSA renal scintigraphy is helpful in diagnosing UTI and vesicoureteral reflux; we recommend VCUG when DMSA scan supports UTI despite a negative urine culture and a normal ultrasongraphy.